CHRONOSTRATIGRAPHIC CORRELATIONS: THEIR IMPORTANCE FOR THE DEFINITION OF GEOCHRONOLOGIC UNITS - Remane J. (My University, 2003)
The present article resumes the philosophy underlying the (re)definition of chronostratigraphic/geochronologic units through their boundaries by working groups of the International Commission on Stratigraphy (ICS), following the ICS Guidelines. With respect to the historical approach, this philosophy implies a change in the way how stages are defined. Stages, originally defined by their contents, are now defined by their lower boundary only: the concept of the Global Stratotype Standard-section and Point (GSSP). As before, stages may be characterized by their contents, but precise definitions of stages and their scope can only be attained via boundary definitions. The following subjects are dealt with in detail: (1) The choice of the level of a chronostratigraphic/geochronologic boundary which is to be defined by a GSSP; this is determined by practical considerations concerning the correlation of the envisaged stratigraphic level. (2) If traditional names are to be preserved, some kind of compromise is always necessary because none of them is clearly and unequivocally defined. This goal can be attained by a democratic vote. (3) Because of gaps and condensation, even the more favorable historical stratotypes are unsuitable for the redefinition of classical stages by their lower boundaries.
Keywords: International Commission on Stratigraphy (ICS); International Stratigraphic Chart; chronostratigraphy; biostratigraphy; biochronology; stage concept; unit-stratotypes; boundary-stratotypes (GSSP); historical stratotypes; chronostratigraphic markers